Unmet needs for care for activities of daily living among older adults with functional disabilities in Vietnam - Phi, Phong Manh; Giang, Long Thanh; Pham, Tham Thi Hong (Frontiers in Public Health, 2023)
Background: Given a low middle-income status, Vietnam is experiencing a rapidly aging population. Along with this demographic trend, care need of older persons, particularly those with functional disability, has become an emerging policy issue.Purpose: This study examined the prevalence of unmet need of care in activities of daily living (ADLs) among the Vietnamese older people with functional disability.We used data from the Population Change and Family Planning Survey (PCS) in 2021, which was a nationally-representative survey. Cross-tabulations and logistic regressions were applied to identify older people's individual and household factors associated with their unmet care needs.Results: Overall, 4.80% of older persons with at least one functional disability needing care to perform one or more ADLs suffered unmet need, in which 2.32% of them did not receive any care and 3.05% of them received insufficient assistance. Logistic regression results revealed that age, sex, place of residence, ethnicity, marital status, education levels, self-rated health were significantly associated with unmet need. The higher risk of having unmet need associated with those at middle age (70-79), men, rural residents, ethnicity minorities, currently unmarried persons, those with less than primary educational level, and those with normal or poor self-rated health.Vulnerable older persons, such as those living rural areas, having poor health status, should be paid attention in order to reduce their unmet needs for ADL assistance.